(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background of the study: Urine is collected in drainage bags. The catheter (tube) in your bladder will serve as the attachment point for your bag. Because of urinary incontinence (leakage), urinary retention (inability to urinate), a surgery that required a catheter, or another medical condition, you can have a catheter and urine drainage bag. objectives: 1. To assess Pre-test knowledge score regarding the management of urinary drainage system among class IV workers. 2. To assess Post-test knowledge regarding management of urinary drainage system among class IV workers. 3. To find an association between socio-demographic variables and knowledge regarding management of urinary drainage system among class IV Workers. Methodology: A Descriptive study was conducted through non probability purposive sampling technique. Demographic data was collected by questionary method, Knowledge questionary and information regarding the Management of urinary catheterization given thorough Information booklet. Results: pre-test outcome Class IV workers had poor knowledge in 90% of cases, average knowledge in 10%, and good knowledge in 0% of cases. Following the distribution of an information booklet, we conducted a post-test. Following a test, the results showed that 20% of participants had bad knowledge, 20% had average knowledge, and 80% had strong knowledge.